Artificial Intelligence in the development strategy of contemporary China - CÉLIO HIRATUKA; ANTÔNIO CARLOS DIEGUES (Brazilian Journal of Political Economy)
ABSTRACT This paper analyzes the role of Artificial Intelligence in the broader context of China’s development strategy, marked by the quest to move to a less capital and more knowledge-intensive model. Chinese Science, Technology, and Innovation policies are discussed, emphasizing endogenous innovation and Artificial Intelligence’s role in this context. Furthermore, some indicators are analyzed to compare China’s current position with other countries, particularly the United States, in terms of Artificial Intelligence knowledge generation, technology development, and business involvement.